Dysfunction in mitochondrial electron transport chain drives the pathogenesis of pulmonary arterial hypertension: insights from a multi-omics investigation - Xin Zhang; Jieling Li; Minyi Fu; Xijie Geng; Junjie Hu; Ke-Jing Tang; Pan Chen; Jianyong Zou; Xiaoman Liu; Bo Zeng (Respiratory Research)
Abstract Background Pulmonary arterial hypertension (PAH) is a progressive disorder that can lead to right ventricular failure and severe consequences. Despite extensive efforts, limited progress has been made in preventing the progression of PAH. Mitochondrial dysfunction is implicated in the development of PAH, but the key mitochondrial functional alterations in the pathogenesis have yet to be elucidated. Methods We integrated three microarray datasets from the Gene Expression Omnibus (GEO), including 222 lung samples (164 PAH, 58 controls), for differential expression and functional enrichment analyses. Machine learning identified key mitochondria-related signaling pathways. PAH and control lung tissue samples were collected, and transcriptomic and metabolomic profiling were performed. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis investigated shared pathways, and canonical correlation analysis assessed gene-metabolite relationships. Results In the GEO datasets, mitochondria-related signaling pathways were significantly enriched in PAH samples, in particular the electron transport chain (ETC) in mitochondrial oxidative phosphorylation system. Notably, the electron transport from cytochrome c to oxygen in ETC was identified as the most crucial mitochondria-related pathway, which was down-regulated in PAH samples. Transcriptomic profiling of the clinical lung tissue analysis identified 14 differentially expressed genes (DEGs) related to mitochondrial function. Metabolomic analysis revealed three differential metabolites in PAH samples: increased 3-phenyllactic acid and ADP, and decreased citric acid. Mitochondria-related genes highly correlated with these metabolites included KIT, OTC, CAMK2A, and CHRNA1. Conclusions Down-regulation of electron transport from cytochrome c to oxygen in mitochondrial ETC and disruption of the citric acid cycle homeostasis may contribute to PAH pathogenesis. 3-phenyllactic acid emerges as a potential novel diagnostic biomarker for PAH. These findings offer insights for developing novel PAH therapies and diagnostics.